2014
DOI: 10.1016/j.crohns.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based therapy for inflammatory bowel disease patients with functional abdominal symptoms or high perceived stress levels

Abstract: NCT01426568.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 47 publications
2
110
0
7
Order By: Relevance
“…Of these, a further 32 were excluded for various reasons leaving 14 studies eligible for data extraction. [23][24][25][26][27][28][29][30][31][32][33][40][41][42] Agreement between reviewers for eligibility assessment was excellent (Kappa statistic = 0.91). Detailed study characteristics are provided in Table 1, and risk of bias across all studies is reported in page 1 of the webappendix.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, a further 32 were excluded for various reasons leaving 14 studies eligible for data extraction. [23][24][25][26][27][28][29][30][31][32][33][40][41][42] Agreement between reviewers for eligibility assessment was excellent (Kappa statistic = 0.91). Detailed study characteristics are provided in Table 1, and risk of bias across all studies is reported in page 1 of the webappendix.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29]32,33,[40][41][42] . Four of these presented data in patients with CD, 25,32,40,42 four in patients with UC, 27,28,40,41 and five in patients with IBD.…”
Section: Quality Of Life In Patients With Quiescent Ibdmentioning
confidence: 99%
See 3 more Smart Citations